Association between service readiness and PMTCT cascade effectiveness: a 2018 cross-sectional analysis from Manica province, Mozambique - Aneth Dinis; Orvalho Augusto; Kristjana H. Ásbjörnsdóttir; Jonny Crocker; Sarah Gimbel; Celso Inguane; Isaías Ramiro; Joana Coutinho; Mery Agostinho; Emilia Cruz; Fernando Amaral; Esperança Tavede; et al. (BMC Health Services Research, 2022)
Abstract Background Despite high coverage of maternal and child  health services in Mozambique, prevention of mother-to-child transmission of HIV (PMTCT) cascade outcomes remain sub-optimal. Delivery effectiveness is modified by health system preparedness. Identifying modifiable factors that impact quality of care and service uptake can inform strategies to improve the effectiveness of PMTCT programs. We estimated associations between facility-level modifiable health system readiness measures and three PMTCT outcomes: Early infant diagnosis (polymerase chain reaction (PCR) before 8 weeks of life), PCR ever (before or after 8 weeks), and positive PCR test result. Methods A 2018 cross-sectional, facility-level survey was conducted in a sample of 36 health facilities covering all 12 districts in Manica province, central Mozambique, as part of a baseline assessment for the SAIA-SCALE trial (NCT03425136). Data on HIV testing outcomes among 3,427 exposed infants were abstracted from at-risk child service registries. Nine health system readiness measures were included in the analysis. Logistic regressions were used to estimate associations between readiness measures and pediatric HIV testing outcomes. Odds ratios (OR) and 95% confidence intervals (95%CI) are reported. Results Forty-eight percent of HIV-exposed infants had a PCR test within 8 weeks of life, 69% had a PCR test ever, and 6% tested positive. Staffing levels, glove stockouts, and distance to the reference laboratory were positively associated with early PCR (OR = 1.02 [95%CI: 1.01–1.02], OR = 1.73 [95%CI: 1.24–2.40] and OR = 1.01 [95%CI: 1.00–1.01], respectively) and ever PCR (OR = 1.02 [95%CI: 1.01–1.02], OR = 1.80 [95%CI: 1.26–2.58] and OR = 1.01 [95%CI: 1.00–1.01], respectively). Catchment area size and multiple NGOs supporting PMTCT services were associated with early PCR testing OR = 1.02 [95%CI: 1.01–1.03] and OR = 0.54 [95%CI: 0.30–0.97], respectively). Facility type, stockout of prophylactic antiretrovirals, the presence of quality improvement programs and mothers’ support groups in the health facility were not associated with PCR testing. No significant associations with positive HIV diagnosis were found. Conclusion Salient modifiable factors associated with HIV testing for exposed infants include staffing levels, NGO support, stockout of essential commodities and accessibility of reference laboratories. Our study provides insights into modifiable factors that could be targeted to improve PMTCT performance, particularly at small and rural facilities.